Evidence that rheumatoid arthritis synovial T cells are similar to cytokine-activated T cells: involvement of phosphatidylinositol 3-kinase and nuclear factor kappaB pathways in tumor necrosis factor alpha production in rheumatoid arthritis. - Brennan, F; Hayes, A; Ciesielski, C; Green, P; Foxwell, B; Feldmann, M (2002)
OBJECTIVE: To investigate the mechanism that leads to the spontaneous production of tumor necrosis factor alpha (TNFalpha) in rheumatoid arthritis (RA) synovial tissue. METHODS: Normal blood monocytes were cocultured either with fixed activated T cells generated from normal blood or RA synovial T cells purified from synovium. TNFalpha production was measured in supernatants from these cocultures following blockade of the transcription factor nuclear factor kappaB (NF-kappaB) using adenoviral transfer of the inhibitor of NF-kappaB kinase alpha into the responding monocytes, or blockade of phosphatidylinositol 3-kinase (PI 3-kinase) using the inhibitory drugs wortmannin or LY294002. TNFalpha production was measured by enzyme-linked immunosorbent assay. RESULTS: TNFalpha production in synovial tissue from patients with RA but not osteoarthritis was found to be T cell dependent. The RA synovial joint T cells resembled normal T cells that had been activated for 8 days using a cocktail of cytokines. These T cells, designated Tck (cytokine-activated T cells), and RA synovial T cells both induced TNFalpha production in resting monocytes in a cell-contact-dependent manner, which was abrogated by blockage of the transcription factor NF-kappaB but augmented if PI 3-kinase was inhibited. Normal blood T cells activated conventionally via the T cell receptor with crosslinked anti-CD3 antibody resulted in TNFalpha production from monocytes; this was unaffected by NF-kappaB blockade, but was inhibited in the presence of PI 3-kinase-blocking drugs. CONCLUSION: These data provide strong evidence for the importance of T cells in inducing TNFalpha in chronic inflammatory rheumatoid tissue, and give insight into the mechanism whereby these T cells are activated in vivo. Furthermore, they indicate that production of TNFalpha in pathologic tissue is regulated differently from physiologic antigen-dependent TNFalpha production, which raises the possibility that selective inhibitors of TNFalpha in disease may be developed.